The importance of Pseudomonas aeruginosa plasmids for the n-alkanes biodegradation ‎ability - Al-Kanany‎, Fadhil N.; Al-Maliki‎, Muntasser M.; Othman‎, Rasha M.; Jaafar‎, Raghad S. (Mesopotamian Journal of Marine Sciences, 2023)
The study was conducted to evaluate the importance of Pseudomonas aeruginosa plasmids in their efficiency for n-alkanes biodegradation. Pseudomonas aeruginosa was isolated and characterized using biochemical and genetic tests, then acridine orange was used as a chemical plasmid curing agent, the loss of plasmids was confirmed by profiling using agarose gel electrophoresis comparing with the wild type, the two bands appear in the gel which located between 3Kbp to 4Kbp refer to the two plasmids harbouring by wild type. The biodegradation efficiency of wild and plasmid cured bacteria was 85% and 81.63% respectively, the study demonstrated that the loss of Pseudomonas aeruginosa plasmids leads to a slight reduction effect of the n-alkanes biodegradation efficiency